2016
DOI: 10.1021/acssuschemeng.5b01163
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Alcohols Using Photoactive VO@g-C3N4

Abstract: A photoactive VO@g-C 3 N 4 catalyst has been developed for the selective oxidation of alcohols to the corresponding aldehydes and ketones. The visible light mediated activity of the catalyst could be attributed to photoactive graphitic carbon nitrides surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 32 publications
(42 reference statements)
0
42
0
Order By: Relevance
“…‐ Recently Sanny et al reported a bimetallic catalyst on a graphitic carbon nitride (AgPd@g‐C 3 N 4 ) for conversion of biomass‐derived levulinic acid under visible light. In a subsequent report they described a photoactive VO@g‐C 3 N 4 catalyst for the C‐H activation and selective oxidation of alcohols to the corresponding aldehydes and ketones …”
Section: Introductionmentioning
confidence: 99%
“…‐ Recently Sanny et al reported a bimetallic catalyst on a graphitic carbon nitride (AgPd@g‐C 3 N 4 ) for conversion of biomass‐derived levulinic acid under visible light. In a subsequent report they described a photoactive VO@g‐C 3 N 4 catalyst for the C‐H activation and selective oxidation of alcohols to the corresponding aldehydes and ketones …”
Section: Introductionmentioning
confidence: 99%
“…Low yields and poor selectivity have been the main drawbacks associated with catalytic oxidation reactions. Recently, the selective oxidation of benzyl alcohols to benzaldehyde by using iron oxide-based nanocomposites [17], ionic liquid-modified MIL-100(Fe) [18], developed copper(Ι)/TEMPO catalysts (TEMPO = 2,2,6,6-tetramethylpiperidinyl-N-oxyl) [19,20], photocatalytic oxidation by homogeneous CuCl2 [21], metal-free systems [22], photoactive VO@g-C3N4 [23] and Co oxide nanoparticles [24], among others have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies concern the photochemical activity and spectroscopic data analysis of g-C 3 N 4 as well as modification of its surface [19], applications to organic transformations are limited. For example, graphitic C 3 N 4 as well as its surface-doped-materials, catalyze a few reactions; a) photoacetalization of aldehydes/ketones [20] b) the Friedel-Crafts reaction of benzene [21] c) oxidation of alcohols using transition metal doped g-C 3 N 4 [22][23][24][25] d) oxidation of sulfides to sulfoxides using oxidized g-C 3 N 4 (CNO). In addition, selective oxidations of benzylic C-H bonds utilizing mesoporous g-C 3 N 4 with N-OH co catalysts have been reported [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%